DNA replication origins in archaea - Wu, Zhenfang; Liu, Jingfang; Yang, Haibo; Xiang, Hua (Frontiers in Microbiology, 2014)
DNA replication initiation, which starts at specific chromosomal site (known as replication origins), is the key regulatory stage of chromosome replication. Archaea, the third domain of life, use a single or multiple origin(s) to initiate replication of their circular chromosomes. The basic structure of replication origins is conserved among archaea, typically including an AT-rich unwinding region flanked by several conserved repeats (origin recognition box, ORB) that are located adjacent to a replication initiator gene. Both the ORB sequence and the adjacent initiator gene are considerably diverse among different replication origins, while in silico and genetic analyses have indicated the specificity between the initiator genes and their cognate origins. These replicator-initiator pairings are reminiscent of the oriC-dnaA system in bacteria, and a model for the negative regulation of origin activity by a downstream cluster of ORB elements has been recently proposed in haloarchaea. Moreover, comparative genomic analyses have revealed that the mosaics of replicator-initiator pairings in archaeal chromosomes originated from the integration of extrachromosomal elements. This review summarizes the research progress in understanding of archaeal replication origins with particular focus on the utilization, control and evolution of multiple replication origins in haloarchaea.